Analisa Preferensi Konsumen Berbelanja di Pasar Malam dan Dampaknya terhadap Peningkatan Kesejahteraan Ekonomi Pelaku Usaha di Kota Samarinda - Arianti, Arianti; Rhussary, Margaretha Lasni (STIE Muhammadiyah Tanjung Redeb, 2019)
This study aims to analyze the factors of consumer preferences for shopping at the night market and the impact of these preferences on improving the economic welfare of night market entrepreneurs in Samarinda City. Sampling in this study was carried out by the method of non-probability sampling with convenience sampling technique, an analysis tool used simple linear regression. The results showed that there are 5 factors that influence consumer preferences in choosing the night market as a place to shop, of the 5 factors, the most dominant factor is the product. The diversity of products provided at the night market is considered to meet consumer expectations. With the Kaiser- Meyer-Olkin (KMO) test and Bartlett's Test, it shows a value of 0.672 so that the factor analysis process is feasible and the Barlett's Test of significance level of 0,000 shows that there is no correlation between variables so that factor analysis can be done. Meanwhile, the impact of consumer preferences on improving economic welfare can be seen from the results of t count of 5.270 with a significance level of 0,000. From the results of the test of the coef icient of determination can be seen by 72.7% increase in welfare of the night market business.